The impact of the relationship between the organization’s life cycle and organizational structure on performance- Field research in the Iraqi banking sector - Fadel Abbas Al-Amiri; Akram Mohsen Al-Yasiri (Iraqi Journal for Administrative Sciences, 2024)
The research aims to study the effect of the relationship between the organization’s life cycle (X) and organizational structure (X) on performance (Y). In order to achieve this, the stages of the organization’s life cycle (birth, growth, maturity, and decline) were adopted based on the division of Hodge & Anthony (Jones (1991), defining the organizational structure as three types: organic, mixed, and mechanistic) by measuring the three dimensions of the structure. (Formalism, centralization and complexity) based on (Hach 1997: 170). As for the dependent variable, which is performance, it was measured according to the indicators specified by the (& Kaplan Norton) model that were used in the research, which are (ROI), productivity, and the rate of development of individuals. . The two independent variables, the organization’s life cycle and organizational structure, were measured using a questionnaire prepared for this purpose, while the dependent variable was measured based on the final data and accounts for the years (1999 - 2002) and (2004). The research was conducted in the Iraqi banking sector and included a sample of (12) banks, including (4) government and (8) private banks, and the number of members of the sample was (78) managers occupying advanced administrative positions. The Spearman correlation coefficient and the t test were used to measure the significance of the relationship between the study variables, and multiple regression analysis, analysis of variance (ANOVA), and the F test were used to determine the significance of the regression equation. R was also used to interpret the amount of influence of the two independent variables. In the dependent variable. The research reached a set of conclusions, including: . Each stage of the organization's life cycle is linked to the type of organizational structure that is most appropriate to the requirements of that stage, and the effect of this link is reflected in performance indicators. The possibility of the organization adopting certain types of organizational structure at each stage of its life cycle, but in a different arrangement between one stage and another and according to the requirements of that stage, and this is evident through the difference in the impact of these relationships on performance indicators. Then the research concluded with a set of recommendations related to its three variables, and others related to future research.